2016
DOI: 10.1002/chem.201601468
|View full text |Cite
|
Sign up to set email alerts
|

Aspartate‐Based CXCR4 Chemokine Receptor Binding of Cross‐Bridged Tetraazamacrocyclic Copper(II) and Zinc(II) Complexes

Abstract: The CXCR4 chemokine receptor is implicated in a number of diseases including HIV infection and cancer development and metastasis. Previous studies have demonstrated that configurationally restricted bis-tetraazamacrocyclic metal complexes are high-affinity CXCR4 antagonists. Here, we present the synthesis of Cu2+ and Zn2+ acetate complexes of six cross-bridged tetraazamacrocycles to mimic their coordination interaction with the aspartate side chains known to bind them to CXCR4. X-ray crystal structures for thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…16,17 We have taken advantage of these properties by designing bis-linked cross-bridged tetraazamacrocycle metal complexes (Fig. 2) that have remarkably efficient binding 16,[18][19][20] to the aspartate side chains of the CXCR4 chemokine receptor, a trans-membrane receptor important to the fusion process of the HIV virus to leukocytes, 17 the metastasis of cancer cells, 21 and other biological processes. 22 Most relevant to this work, we have shown that a dinickel complex, the meta analogue of ligand 7 (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 We have taken advantage of these properties by designing bis-linked cross-bridged tetraazamacrocycle metal complexes (Fig. 2) that have remarkably efficient binding 16,[18][19][20] to the aspartate side chains of the CXCR4 chemokine receptor, a trans-membrane receptor important to the fusion process of the HIV virus to leukocytes, 17 the metastasis of cancer cells, 21 and other biological processes. 22 Most relevant to this work, we have shown that a dinickel complex, the meta analogue of ligand 7 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the significant challenges in production of X-ray quality bis-linked tetraazamacrocycle complex crystals, 18,23 single-macrocycle transition metal complexes are often used as models. 16,[18][19][20]23 To provide the most accurate model for our bis-macrocycle antagonists, which are linked through a xylene linker, we have synthesised a number of monobenzyl and dibenzyl 4 pendant arm containing cross-bridged tetraazamacrocycles (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of some of the cross-bridged tetraazamacrocycle mono-and bisligands, precursors, and complexes (compounds 1 to 18) was conducted on the basis of methods described in the literature (29,33,34,39 Archibald, submitted for publication). The mono-and bisquinoline derivatives of macrocyclic polyamines (compounds 19 to 26) were synthesized and purified by chromatography and/or solvent crystallization according to the methods that we described earlier (22,30) and were recovered in moderate to good yields.…”
Section: Discussionmentioning
confidence: 99%
“…Macrocyclic polyamines deserve great interest as ligands for transition metal ions. Cross‐bridged cyclams ( L‐R,R′ in Figure a) represent an excellent instance of the class, as their cleft‐like structure allows the lone pairs of the four nitrogen atoms to converge, thus becoming suitable to chelate a metal ion (Figure b).…”
Section: Introductionmentioning
confidence: 99%
“…Cross bridged cyclam ligands have been first investigated by Weisman, who reported a detailed synthesis of the dimethyl species L‐Me,Me Busch and co‐workers used both the dimethyl and dibenzyl L‐Bn,Bn ligands to coordinate mid‐late transition metals, getting complexes useful for different applications: manganese compounds were largely discussed in patent literature as bleach catalysts, while copper complexes found application in radiopharmaceutical and medical fields …”
Section: Introductionmentioning
confidence: 99%